Influence of carbon dot synthetic parameters on photophysical and biological properties. Issue 25 (16th June 2021) - Lesani, Pooria; Lu, Zufu; Singh, Gurvinder; Mursi, Maya; Mirkhalaf, Mohammad; New, Elizabeth J.; Zreiqat, Hala
Abstract : Optimization of the carbon dots synthetic parameters, including type of solvent, heating time, dopant quantity, and particle size distribution range, to gain a better understanding of their effect on carbon dots photophysical and biological behavior. Abstract : Recently, carbon dots (CDs) have been widely investigated for biological applications in imaging. One-step hydrothermal synthesis is considered to be one of the most promising methods for the synthesis of CDs, due to its simple and rapid manipulation, flexible selection of ingredients, environmentally friendly conditions, and low-cost. A number of synthetic and post-synthetic parameters, including solvent, heating time, dopant quantity, and particle size distribution, play a crucial role in controlling the size and surface structure of CDs, which ultimately have influence on their photophysical and biological behavior. Despite the crucial role of each of these parameters in defining the yield and nature of synthesized CDs, they have not previously been rigorously optimized, particularly with respect to desired biological applications. Herein, we report our comprehensive optimization of the parameters employed for the hydrothermal synthesis of CDs to gain a better understanding of the effect of these parameters on optical properties, cytotoxicity, and cellular uptake efficiency. Furthermore, this work will open up new pathways toward the design of CDs with physiochemical properties tailored for specific biomedical applications such as bioimaging.